Institute to Frontline ICU Quality. Issue 3 (July 2021) - McGonigal, Michelle; Snyder, Amy
Abstract : Organizational structures have been shifting in health care over the past decade. Although hierarchal structures exist in many hospitals and health care entities, matrix approaches have been implemented to complement the traditional reporting configuration. The institute model is a hybrid structure implemented within medical and surgical service lines to promote patient-centered care within a hospital network. Physician administrators lead the institutes with collaboration by key liaisons such as nursing and quality leaders. In order to be successful, the concepts must extend from the boardroom to the front line. Teams focused specifically on quality metrics were developed within the service lines using an interdisciplinary approach to promote engagement and achieve desired outcomes. A key strategy was the implementation of a nurse manager/attending physician dyad model. This partnership is the linkage from the front line to the institute chair. The focus on collegiality and collaboration has led to improved engagement and problem-solving within the service lines.